Penyegaran Pemahaman Tuberkulosis Paru Bagi Kader Kesehatan di Kelurahan Tanjung Raya Kecamatan Kedamaian Kota Bandar Lampung Tahun 2024 - Syahrul Hamidi Nasution; Fajriani, Indah; Nasution, Helmi Suryani; Musyabiq, Sofyan (JPM (Jurnal Pengabdian Masyarakat) Ruwa Jurai, 2024)
Tuberculosis (TB) is a chronic infectious disease caused by bacteria (Mycobacterium tuberculosis) and usually attacks the lungs. Tuberculosis (TB) is one of the top 10 causes of death globally. Indonesia is still ranked third in the world and is one of the biggest challenges facing Indonesia and requires attention from all parties, because it causes a high burden of morbidity and mortality. One effort that can be made is strengthening the understanding of TB among health cadres who are part of health services in the community. The service activities carried out include measuring prior knowledge (pre test and post test), counseling for posyandu cadres with the aim of information obtained by health cadres being disseminated to sufferers and their families in the community. The activity was attended by 10 health cadres, after the outreach there was a 30% increase in knowledge about tuberculosis.Keywords: health cadres, counseling, tuberculosis.